2008
DOI: 10.1007/s11748-007-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair for infective endocarditis

Abstract: MV repair is feasible in patients with both active and healed IE. MV repair preserves better LV function and structure postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…An additional concern related to the use of patches for valve repair relates to the technical challenges associated with the implantation. Omoto and colleagues 30 reported a high rate of reoperations (20%) for patch dehiscence, which was hypothesized to be related to the extensive suture line length in large patches. In the current study, a suture line leak developed in only 1 patient, but no additional patients showed evidence of patch dehiscence.…”
Section: Commentmentioning
confidence: 99%
“…An additional concern related to the use of patches for valve repair relates to the technical challenges associated with the implantation. Omoto and colleagues 30 reported a high rate of reoperations (20%) for patch dehiscence, which was hypothesized to be related to the extensive suture line length in large patches. In the current study, a suture line leak developed in only 1 patient, but no additional patients showed evidence of patch dehiscence.…”
Section: Commentmentioning
confidence: 99%
“…Although better feasibility of MV repair has been demonstrated in patients with healed IE than in those with active IE, surgery during the active phase of IE should frequently be selected to prevent additional thromboembolic events, minimize ongoing valvular destruction, and achieve earlier relief of acute volume overload to the left ventricle (LV) caused by mitral regurgitation (MR). 1,2 The combination of autologous pericardial patch repair, artificial chordal replacement, and annuloplasty has enabled complex MV repair, but suture stress on inflamed valve tissues may result in recurrence of MR. 1 If the feasibility of MV repair appears uncertain, based on preoperative echocardiography, it should not be recommended as an elective operation, but may be preferred in patients with active IE and high-risk comorbidities, such as neurological, hematological, or immunological complications. This study reviewed the results of surgery in patients in the active phase of native mitral valve IE.…”
Section: Introductionmentioning
confidence: 99%
“…Enlarging the AML by autologous pericardial patch 3) and chordae replacement with ePTFE 2) showed good durability. An autologous pericardium fixed with glutaraldehyde is widely used in MV repair for active infective endocarditis in our institute, 4) and restriction or calcification has not been demonstrated by follow-up echocardiography. Combinations of chordae replacement, ring annuloplasty and AML augmentation may increase the feasibility of MV repair for rheumatic MV disease.…”
Section: Discussionmentioning
confidence: 94%